Table2Charts: Recommending Charts by Learning Shared Table Representations - Zhou, Mengyu; Li, Qingtao; He, Xinyi; Li, Yuejiang; Liu, Yibo; Ji, Wei; Han, Shi; Chen, Yining; Jiang (姜大昕), Daxin; Zhang, Dongmei (The 27th ACM SIGKDD Conference on Knowledge Discovery and Data Mining (KDD ’21), 2021)
It is common for people to create different types of charts to explore a multi-dimensional dataset (table). However, to recommend commonly composed charts in real world, one should take the challenges of efficiency, imbalanced data and table context into consideration. In this paper, we propose Table2Charts framework which learns common patterns from a large corpus of (table, charts) pairs. Based on deep Q-learning with copying mechanism and heuristic searching, Table2Charts does table-to-sequence generation, where each sequence follows a chart template. On a large spreadsheet corpus with 165k tables and 266k charts, we show that Table2Charts could learn a shared representation of table fields so that recommendation tasks on different chart types could mutually enhance each other. Table2Charts outperforms other chart recommendation systems in both multi-type task (with doubled recall numbers R@3=0.61 and R@1=0.43) and human evaluations.